Genetically improved varieties of Pleurotus pulmonarius (Fries) Quélet by molecular and breeding techniques / Farhat Ahmadi Avin - Avin, Farhat Ahmadi (2014)
Pleurotus pulmonarius (Fries) Quélet, also known P. sajor-caju (Fries) Singer, is a valuable edible mushroom, commonly called the grey oyster mushroom. Although there is substantial market demand for this mushroom in Malaysia, there has not been much systematic study of the breeding and production of new improved hybrids. Hence, in the current study, the main objective was to generate high performance varieties of P. pulmonarius via a cross-breeding programme. The results of the preliminary analysis of variance showed highly significant differences (p ≤ 0.01) among the crosses of P. pulmonarius for almost all phenotypic traits measured. Therefore, construction and analysis of data based on a diallel cross for all the evaluated characteristics was possible. In the current study, levels of hybrid vigour for early fruiting, yield, percentages of contaminated bags and bags that had successful fruiting, shape of sporocarps, post-harvest handling storage value of sporocarps and other morphological traits were examined in the F1, F2 and F3 generations. Based on the results, out of 231 crosses done, 88 combinations were compatible and, of these, 46 hybrids were able to form sporocarps. After evaluation and scoring of the obtained hybrids, three best hybrid varieties (3A2-2A1, 3B1-2A1 and 3A2-2B4) were eventually selected. The superiority of the selected hybrids over the parental varieties was reflected in the higher levels of mean and heterosis effects they exhibited. This showed that the final selected hybrid varieties had high positive percentage of heterosis for most of the valuable breeding traits such as days for primordia to appear, for sporocarps to mature and for harvesting, yield, percentage of contaminated bags and bags that had successful fruiting. The effects of general combining ability (GCA) were not significant for all the traits measured, while the effects of specific combining ability (SCA) were statistically significant (p ≤ 0.01). Moreover, the results of genetic variance components and heritability indicated that a large part of the total genetic variation observed for most traits was associated with genes which were dominant in their effects. Similarly, lower levels of narrow-sense heritability, for most of the traits were observed, while for broad-sense heritability these levels were extremely high (at least 0.71). These results showed the importance of high dominance values on heterosis on the other hand, and on selection of the proper breeding method which was the hybrid production on the other. The results of the correlation analysis were supported by the implementation of the indirect breeding principle for the more strongly associated characteristic. To achieve the main objective of the current study, the first and most important step of a successful cross-breeding programme was to identify the taxonomic position of the parental species. Partial rDNA sequences, including internal transcribed spacer (ITS) regions, were used for this aim of study to assess the phylogenetic relationships of selected edible species of Basidiomycetes. Phylogenetic trees showed five distinct clades; each clade belonging to a separate family group. Moreover, different species of each family were placed in distinct sub-clusters. In short, polymorphism occurred throughout the ITS regions due to insertion-deletion and point mutations, and could be clearly differentiated within families as well as within genera. Secondly, the parental varieties were selected by a combination of the two highly variable regions of intergenic spacer (IGS) 1 and internal transcribed spacer (ITS) 1 & 2. The integration of these two regions made it possible not only to distinguish species but also to identify intra-species variation reasonably well. Another concern in any mushroom hybridisation programme is how to identify compatible mating partners. In the current study, the 5′ end of intergenic spacer (IGS) 2 region was used to identify different single spore isolates (SSIs). With the amplification of this region, the selected monokaryotic isolates of P. pulmonarius were clearly categorized into two distinct groups (type A and B). Moreover, the dikaryotic isolates were able to produce double-banded PCR products, while the monokaryons created only one unique amplicon. This study used the candidate region approach to enable a pedigree history to be recorded. Furthermore, the morphological and molecular (COX1 gene) assessments were used to identify the newly generated hybrid varieties from their relative parental varieties. The efficiency of the sequences of COXI gene was also clearly shown and the selected hybrid varieties were clearly distinguished. In conclusion, based on the various evidences gathered and analyses including mean comparisons and heterosis, it was clear that the three novel hybrid varieties of 3A2-2B4, 3A2-2A1 and 3B1-2A1 were greater compared to the other varieties, as well as than their own parents.